The role of visual symmetry between contemporary art and AI-generated methods in promoting sustainable visual culture. (Al-Academy, 2025)
The current research addresses the role of visual symmetry between contemporary art and methods generated by artificial intelligence in promoting sustainable visual culture. Visual symmetry embodies the convergence in compositional structures between human artistic expression patterns and those generated by intelligent algorithms, which opens new horizons in redesigning the aesthetic and visual awareness of the recipient. The current research seeks to answer the following question: What is the role of visual symmetry between contemporary art and methods generated by artificial intelligence (AI) in promoting sustainable visual culture? The aim of the research was to reveal the role of visual symmetry between contemporary art and methods generated by artificial intelligence (AI) in promoting sustainable visual culture. The chapter concludes by defining the boundaries of the research and defining the terms. The second chapter included four main topics: the first topic: pictorial symmetry; the second topic: sustainable development; the third topic: visual culture and its relationship to sustainable development; and the fourth topic: cultural symmetry between artificial intelligence and art. The chapter concluded with indicators of the theoretical framework.The third chapter dealt with the research methodology and procedures. The researchers defined their research community as (261) male and female students from Iraqi universities (Baghdad, Babylon, and Al-Mustansiriya), in the art education departments, for the academic year (2024-2025 AD). The research sample was defined as (100) male and female students. A scale consisting of (25) artworks was designed and applied to the research sample. In the fourth chapter, the researchers reviewed the most prominent results of the research, including: There is a clear tendency among students at the universities of Baghdad and Babylon to prefer original paintings, while students at Al-Mustansiriya University showed a convergence in preference between original paintings and those produced by artificial intelligence. This indicates that sustainable visual culture may be linked to environmental or cognitive factors that vary from one university to another, opening the door to deeper analytical studies to explore the determinants of visual taste and interaction with digital arts. The research conclusions were: that students distinguished between "mastery" and "meaning." Despite the technical precision of artificial intelligence, it does not possess the emotional memory or cultural reference of a human artist. This is an indicator of the sustainability of critical taste in the face of technical fascination, the limitations of artificial intelligence in expressing symbolic depth, and the students' appreciation of works that carry value and a message, whether original or digital.